2019
DOI: 10.1111/cts.12709
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Risk of Sinusoidal Obstruction Syndrome of the Liver after Busulfan‐Cyclophosphamide Conditioning Prior to Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: The aim of this study is to evaluate the incidence of sinusoidal obstruction syndrome (SOS) of the liver and the clinical outcome after hematopoietic stem cell transplantation (HSCT) based on several modifications in our protocols. We retrospectively investigated 372 patients undergoing myeloablative conditioning with oral busulfan (Bu) and cyclophosphamide before allogeneic HSCT during 1990–2015. Patients' supportive care was changed in order to reduce the regimen‐related toxicities. Norethisterone use was te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
(92 reference statements)
1
8
0
Order By: Relevance
“…About 60% of all patients transplanted between 2013 and 2020 were conditioned with Bu, almost all of them to treat myeloid neoplasms (i.e., 95%). Bu PK dosing started in the 2000’s and introduced as TDM in the following years, allowing an important reduction of hepatic toxicity and the SOS, as the incidence of SOS has been reduced from about 15 to 3% in <10 years [ 4 , 18 ]. Our target-AUC was reached in only 46% of the time, but we used narrower target limits than others (i.e., 800–1500 μmol/l*min [ 23 ], 900–1520 μmol/l*min [ 26 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 60% of all patients transplanted between 2013 and 2020 were conditioned with Bu, almost all of them to treat myeloid neoplasms (i.e., 95%). Bu PK dosing started in the 2000’s and introduced as TDM in the following years, allowing an important reduction of hepatic toxicity and the SOS, as the incidence of SOS has been reduced from about 15 to 3% in <10 years [ 4 , 18 ]. Our target-AUC was reached in only 46% of the time, but we used narrower target limits than others (i.e., 800–1500 μmol/l*min [ 23 ], 900–1520 μmol/l*min [ 26 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Bu pharmacokinetics (Bu-PK) after intravenous Bu administration is performed since 2013 in Basel as standard therapeutic drug monitoring (TDM), permitting a dose individualization for each patient according to the calculated area-under-the-curve (AUC) [ 17 ]. TDM has permitted to decrease mainly hepatic toxicity and especially the incidence of SOS, which plays an important role in non-relapse mortality (NRM) [ 4 , 18 ]. Since April 2019, Bu infusion was switched from 4 times daily (Bu-4) to once daily (Bu-1) in Basel, as this is more comfortable for application without showing an increase prevalence in toxicity or end-organ damage [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of ursodeoxycholic acid is considered useful in the prophylaxis and treatment of some liver conditions, especially from DECH for being one of the reasons that may lead to the need for HSCR according to the results presented by this study. A retrospective study investigated the use of ursodeoxycholic acid and found a decreased incidence of sinusoidal obstruction syndrome and other liver complications 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The hepatotoxicity of BuCy regimen is well described [12][13][14]26]; one of the pathomechanism of the hepatotoxicity of Bu and Cy is the depletion in glutathione levels, which plays a central role in the metabolism of the toxic metabolites of Cy in hepatocytes [9,10]. Glutathione depletion as a mechanism of hepatic toxicity had been studied extensively [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that inter-individual discrepancy of pharmacokinetics of busulfan impacts on toxicity outcomes [ 31 33 ]. The introduction of busulfan therapeutic drug monitoring between 2000 and 2010 led to a reduction in adverse outcomes regarding liver toxicity, highlighted by a reduction in the VOD incidence from 15% in the late 1990s to 3% after 2010 after dose adjustment of busulfan during this time period [ 26 , 31 ]. In our trial, the incidence of severe VOD is 1.4% (one case in 70 patients) and this is comparable to the literature, where incidence of 2-5% has been described [ 26 , 34 ].…”
Section: Discussionmentioning
confidence: 99%